Interactions between Natural Health Products and Oral Anticoagulants: Spontaneous Reports in the Italian Surveillance System of Natural Health Products. (9th January 2011) - Paoletti, Angelica; Gallo, Eugenia; Benemei, Silvia; Vietri, Michele; Lapi, Francesco; Volpi, Roberta; Menniti-Ippolito, Francesca; Gori, Luigi; Mugelli, Alessandro; Firenzuoli, Fabio; Vannacci, Alfredo
Abstract : Introduction . The safety of vitamin K antagonists (VKA) use can be compromised by many popular herbal supplements taken by individuals. The literature reports that 30% of warfarin-treated patients self-medicates with herbs. Possible interactions represent an health risk. We aimed to identify all herbs-oral anticoagulants interactions collected in the Italian database of suspected adverse reactions to "natural health" products. Methods . The Italian database of spontaneous reports of suspected adverse reactions to natural products was analyzed to address herb-VKAs interactions. Results . From 2002 to 2009, we identified 12 reports with 7 cases of INR reduction in patients treated with warfarin (n = 3 ) and acenocoumarol (n = 4 ), and 5 cases of INR increase (all warfarin associated). It was reported 8 different herbal products as possibly interacting. Discussion . Our study confirms the risk of interactions, highlighting the difficulty to characterize them and their mechanisms and, finally, prevent their onset. The reported data underline the urgent need of healthcare providers being aware of the possible interaction between natural products and VKA, also because of the critical clinical conditions affecting patients. This is the first step to have the best approach to understand possible INR alterations linked to herb-VKA interaction and to rightly educate patients in treatment with VKA.